2012
DOI: 10.1139/y2012-079
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose theophylline restores corticosteroid responsiveness in rats with smoke-induced airway inflammation

Abstract: Patients with chronic obstructive pulmonary disease (COPD) respond poorly to corticosteroids. Histone deacetylase-2 (HDAC-2) plays a pivotal role in many cases of steroid insensitivity. The main aim of this study was to restore the smoking-induced reduction in corticosteroid sensitivity by increasing HDAC-2 activity using low-dose theophylline. Rats were exposed to cigarette smoke (CS) and treated with budesonide and two doses of theophylline. Besides the pathologic examination and cell counting in the broncho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 40 publications
5
17
0
Order By: Relevance
“…Reversal of corticosteroid resistance in COPD patients by restoring HDAC2 levels has proved to be effective. In this regard, it has been reported that theophylline and phosphoinositide-3 kinase inhibitors could reverse steroid resistance by increasing HDAC2 expression 16,17. Consistent with previous reports,18,19 the present study demonstrated that cigarette smoke inhibited HDAC2 expression.…”
Section: Discussionsupporting
confidence: 92%
“…Reversal of corticosteroid resistance in COPD patients by restoring HDAC2 levels has proved to be effective. In this regard, it has been reported that theophylline and phosphoinositide-3 kinase inhibitors could reverse steroid resistance by increasing HDAC2 expression 16,17. Consistent with previous reports,18,19 the present study demonstrated that cigarette smoke inhibited HDAC2 expression.…”
Section: Discussionsupporting
confidence: 92%
“…Nortriptyline, a tricyclic antidepressant, has been shown to restore corticosteroid sensitivity induced by cigarette smokemediated oxidative stress, which is associated with increased HDAC activity (81). Low concentration of theophylline restores corticosteroid responsiveness in rats with smoke-induced airway inflammation and increases HDAC2 activity in alveolar macrophages from patients with COPD (23,114). A recent clinical trial has demonstrated that a combination therapy with an inhaled corticosteroid and low-dose of theophylline attenuated airway inflammation in patients with COPD (32).…”
Section: Hdac2 In Inflammation and Steroid Resistancementioning
confidence: 99%
“…Furthermore, the expression of IL-8 and TNF-α in the lung tissue was negatively correlated with HDAC2 expression, suggesting that HDAC2 is involved in the modulation of inflammatory cytokine release in the context of airway inflammation. Since HDAC dysfunction may be associated with corticosteroid resistance in COPD (8,9,11,12), in the present study, the synergetic effect of the TCHM and glucocorticoid on the expression of HDAC2 as well as inflammatory mediators (IL-8 and TNF-α) in the lungs of the COPD rat model was further explored. The TCHM plus budesonide significantly blocked the suppression of HDAC2 expression in the lungs in response to the intratracheal instillation of LPS plus cigarette smoke exposure, while budesonide treatment alone did not.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of corticosteroid resistance may involve the imbalance of histone acetylation/deacetylation, oxidative stress and genetic or epigenetic alterations (9,10). In this study, histone deacetylase 2 (HDAC2) dysfunction is thought to play an important role in the development of corticosteroid resistance in COPD (8,9,11,12). Thus, increasing HDAC2 activity may be a promising strategy to overcome corticosteroid resistance in COPD.…”
Section: Introductionmentioning
confidence: 95%